SWEARING WORDS ON YOUTUBE COMMENT COLUMN IN CNN POLITICAL NEWS - Febby Halimah Lubis; Ridwan Hanafiah; Dian Marisha Putri (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
This study aimed to identify the types of swearing words and the reasons of swearing words that are used on YouTube comment column. This study conducted a descriptive qualitative research. The source of the data was taken from comment column of video uploaded by CNN about political news on YouTube. In analyzing the data, the researchers employed the theory proposed by Lakoff (1975) in order to identify the types of swearing word and the theory of Andersson (in Karjalainen, 2002:23)  in order to describe the reasons of swearing word. The result of this study revealed that there were two types of swearing word, which were strong and weak swearing word and three reasons of swearing words, which were psychological, social and linguistic motive. The most dominant type was strong swearing word and the most dominant reasons of using swearing word was psychological motive. The word fuck as the powerful taboo word was the most dominant word contained in the expressions of swearing word.